Kanjuruhan Football Disaster in News Framing of Kumparan+ and Kompas.id - Rizqi, Aldi Aprilla Nur; Junaedi, Fajar (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2023)
This study aims to analyse how the online media Kumparan+ and Kompas.id reported on the riots in Kanjuruhan Malang. The Kanjuruhan tragedy is a disaster in Indonesian football. One hundred thirty-five football fans died after rioting after the match between Arema FC and Persebaya Surabaya at the Kanjuruhan Stadium. The research method is the framing analysis model of William A. Gamson and Andre Modigliani. This study found that Kumparan+ and Kompas.id framed the news about the Kanjuruhan tragedy as a major disaster in football. Kumparan+ and Kompas.id packaged the framing that the violence at the Kanjuruhan stadium was the leading cause of the tragedy. The use of tear gas by the police has increased the number of victims. Kumparan+ stated that the poor facilities at the stadium, especially the exit doors, caused chaos at the Kanjuruhan stadium. Kompas.id also emphasizes the public's disappointment with the handling of the Kanjuruhan tragedy. This research found that the framing by the Kumparan+ and Kompas.id media had different views in reporting the same event. This can be seen from the analysis results, which show that in its reporting regarding the riots in Kanjuruhan, Kumparan+ identified itself with the team supporters. Meanwhile, Kompas.id identifies with the Indonesian people who view this riot case as the responsibility of all parties involved.